Attitudes Toward Dating Violence in Early and Late Adolescents in Concepción, Chile - Valdivia-Peralta, Maruzzella (Journal of interpersonal violence, 2021)
This study compares attitudes toward teen relationship (or dating) violence (TRV) between early and late adolescents in the province of Concepción, Chile. The sample consisted of 770 adolescents, aged between 11 and 19 with an average age of 14.8 years old, of which 389 were female (50.5%) and 381 were male (49.5%). An adapted version of the Scale of Attitudes Towards Intimate Violence was used. Results found greater justifying attitudes toward violence in early adolescents than in late adolescents, in 6 of 12 items of the scale, with a statistical significance of p ≤ .001 in 4 items and in the overall score, and p ≤ .05 in 2 items. In the comparison according to sex, male adolescents tended to justify violence more than female adolescents did in one item (p ≤ .001). In dating/no dating comparison, statistically significant differences were found in just 2 items, in favor of those who are not in a relationship (p ≤ .05). These results are analyzed and discussed in relation to previous literature. Finally, orientations to future interventions are proposed, and it is suggested that aspects related to sampling and possible modulating variables such as cognitive development and moral development be considered for future investigations.